Case Report: Chronic inflammatory demyelinating polyradiculoneuropathy rather than hemophagocytic lymphohistiocytosis—the initial phenotype of PRF1 gene mutation - Hu, Lin-Yan; Wan, Lin; Wang, Qiu-Hong; Shi, Xiu-Yu; Meng, Yan; Yang, Xiao-Fan; Yang, Guang; Zou, Li-Ping (Frontiers in Immunology, 2023)
Perforin is essentially involved in the granule-dependent killing activities of cytotoxic T lymphocytes and NK cells. Monoallelic PRF1 mutation increases the risk of autoimmune diseases, and biallelic PRF1 mutation causes familial hemophagocytic lymphohistiocytosis-2. Here, we report a case of a 12-year-old girl with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), followed by a rapidly progressive onset of hemophagocytic lymphohistiocytosis (HLH) 9 months later, alongside manifestations of demyelinating encephalopathy. Genetic sequencing revealed a heterozygous nonsense mutation in the PRF1 gene (c.984G>A; p.W328*) and a heterozygous missense mutation in the PRF1 gene (c.1349C>T; p.T450M). Eventually, she died because of no suitable allogeneic hematopoietic stem cell available in time. Our observations suggest that CIPD might represent the initial phenotype of biallelic PRF1 mutation and could serve as an early sign of subsequent HLH. A comprehensive understanding of this condition is paramount for timely diagnosis, treatment, and ultimately improved patient outcomes.